Effect of music therapy on behavioral and physiological neonatal outcomes: A systematic review and dose-response meta-analysis. - Fatemeh Shahbazi; Marzieh Fattahi-Darghlou; Samad Moslehi; Minoo Dabiri-Golchin; Marjan Shahbazi (PLoS ONE)
Background Previous studies have documented the effectiveness of music therapy in improving adverse neonatal outcomes in premature infants. However, this review aims to address the question of how long listening to music can enhance these neonatal outcomes. Methods To conduct this dose-response meta-analysis, we searched the PubMed, Scopus, Web of Science, and Cochrane Library databases. The inclusion criteria comprised randomized clinical trials that investigated the effects of music therapy on improving adverse neonatal outcomes. Preterm infants were defined as those born between 27 and 37 weeks of gestation, as fetuses are known to respond to auditory stimuli starting at the 27th week of pregnancy. The initial search was performed on January 28, 2024, and there were no restrictions on the time frame for the search. Ultimately, we employed a two-stage random effects model using the "drmeta" package in Stata software to perform this dose-response meta-analysis. Results In total, 30 articles (1855 participants) were identified for inclusion in our meta-analysis. According to pooled analysis with each minute increase in music therapy, the means of respiratory rate, pain score, SBP, DBP, behavioral score, and body temperature decrease by 35.3 beats per minutes, 15.3 VAS, 30.7 mmHg, 8.9 mmHg, 2.7, and 0.27°C. On the other hand, with each minute increase in listening to the music, the mean of O2 saturation, heart rate and sleep duration increase 1.7%, 89.2 beats per minutes and 5.081 minutes per day, respectively. Conclusion Music therapy improves the neonatal outcomes of O2 saturation, heart rate, respiratory rate, sleep duration, body temperature and systolic and diastolic blood pressures. Therefore, the existence of a dose-response relationship can indicate a causal relationship between music therapy and the improvement of neonatal outcomes.